2019
DOI: 10.1002/jor.24489
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Muscle Size Following ACL Injury and Reconstruction: A Systematic Review

Abstract: Image‐based assessments of quadriceps muscle size facilitate examination of structural changes after anterior cruciate ligament (ACL) injury and reconstruction (ACLR). Understanding the effects of ACLR on muscle size measures may aid in clarifying the contribution of quadriceps atrophy toward quadriceps strength. The purpose of this study was to systematically review the literature examining the effects of ACLR on quadriceps muscle volume and cross‐sectional area (CSA). An online database search was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 51 publications
(160 reference statements)
2
26
0
Order By: Relevance
“…Gumucio et al 75 obtained vastus lateralis muscle biopsies 1, 2, and 6 months after ACLR, which revealed that individual myofibers had impaired intrinsic force generation capacity as reflected by reduced specific tension (force/CSA). Given that muscle volume and cross-sectional area, and muscle fascicle pennation angle influence maximal muscle force generation capacity, 18,19 it is likely that these morphological changes contribute to the RFD deficits described here in the knee extensor 90 and knee flexor 82,88,89,94,[96][97][98] muscles after ACLR.…”
Section: Aclr and Intrinsic Muscular Factors Affecting Rfd Between-mentioning
confidence: 89%
See 1 more Smart Citation
“…Gumucio et al 75 obtained vastus lateralis muscle biopsies 1, 2, and 6 months after ACLR, which revealed that individual myofibers had impaired intrinsic force generation capacity as reflected by reduced specific tension (force/CSA). Given that muscle volume and cross-sectional area, and muscle fascicle pennation angle influence maximal muscle force generation capacity, 18,19 it is likely that these morphological changes contribute to the RFD deficits described here in the knee extensor 90 and knee flexor 82,88,89,94,[96][97][98] muscles after ACLR.…”
Section: Aclr and Intrinsic Muscular Factors Affecting Rfd Between-mentioning
confidence: 89%
“…Studies have described reduced knee extensor muscle volume and cross-sectional area following ACLR compared to the uninjured side 90 and to healthy controls. 91 Similar findings have been described for the knee flexor muscles when compared to the uninjured side [92][93][94][95][96][97][98] and uninjured controls.…”
Section: Aclr and Intrinsic Muscular Factors Affecting Rfd Between-mentioning
confidence: 99%
“…In the field of sport medicine, quadriceps MV partly explains persistent weakness after ACL injury (46) and atrophy of the quadriceps muscles negatively impacts knee extension strength (12). A valid measure of MV could be applied to monitor progress after ACL reconstruction and assist in return-to-play decisions by giving clinicians a quick and simple prediction of the athletes MV.…”
Section: Prediction Equations Being Specific For the Population Is Imentioning
confidence: 99%
“…Even with guided rehabilitation, atrophy and strength deficits of the quadriceps femoris muscle were reported up to one year after ACL surgery [ 1 3 ] and even longer in subjects with chronically insufficient ACL [ 4 ]. Prolonged quadriceps weakness could only partially be explained by rather small reductions in quadriceps muscle mass indicating a discrepancy between the regain in quadriceps muscle mass and quadriceps strength [ 2 , 5 , 6 ]. This discrepancy might partly be due to impaired neuromuscular function, which is observed after ACL injury [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%